Governor Jerry Brown Speaking at Fulton Mall Rally - Watkins, Howard::::::::: (1978)
Campaign stop, Mayor Daniel Whitehurst, State Senator George Zenovich, Governor Jerry Brown, State Senator Rose Ann Vuich on Free Speech Area stage Banner says "Best Gov. In History"